Early clinical outcomes of the PERIQxA multicentre randomised double-blind trial evaluating postoperative antibiotics after perianal abscess drainage - V. Polaino-Moreno; B. Ruiz-Antorán; A. F. Caballero-Bermejo; M. Artés-Caselles; M. Kraft; J. Serrano-González; X. Remírez-Arriaga; J. L. Lucena-de la Poza; A. Sánchez-Movilla (International Journal of Colorectal Disease, 2026)
Abstract Background Anal fistula frequently develops following surgical drainage of a first cryptoglandular perianal abscess. The role of postoperative antibiotics in preventing fistula formation remains uncertain. Methods PERIQxA is a multicentre, randomised, double-blind, placebo-controlled trial evaluating postoperative amoxicillin–clavulanate compared with placebo after surgical drainage of a first cryptoglandular perianal abscess. This report presents early clinical outcomes from the ongoing trial. Adults without systemic infection or immunosuppression were randomised 1:1 to receive oral amoxicillin–clavulanate (875/125 mg) or placebo every 8 h for 7 days. The primary outcome was anal fistula formation at 6 months. Results Between March 2022 and May 2025, 65 participants were randomised. One participant withdrew consent and was excluded from all analyses. Fifty-seven participants (28 antibiotic, 29 placebo) were included in the primary analysis. At 6 months, anal fistula developed in 21.4% of participants allocated to amoxicillin–clavulanate and 31.0% allocated to placebo (odds ratio [OR] 0.61, 95% confidence interval [CI] 0.18–2.01). At 12 months, fistula formation occurred in 28.6% and 41.4% of participants, respectively (OR 0.57, 95% CI 0.19–1.71). Lower rates of anal fistula formation were consistently observed in the antibiotic group at both time points, although these differences did not reach statistical significance. Obesity (body mass index > 30 kg/m 2 ) was associated with fistula formation. No antibiotic-related safety concerns were identified. Conclusions In this early analysis of the ongoing PERIQxA trial, lower rates of anal fistula formation were observed among participants allocated to postoperative amoxicillin–clavulanate compared with placebo at both 6 and 12 months of follow-up, although these differences did not reach statistical significance. Given the limited sample size, these findings should be interpreted with caution and require confirmation. Additional evidence from PERIQxA, together with other ongoing randomised studies, will help clarify the role of postoperative antibiotic therapy in preventing anal fistula formation after perianal abscess drainage. Trial registration EU Clinical Trials Information System, 2024-520193-35-00.